Dyfuzja wiedzy jawnej i niejawnej w sieciowej organizacji gminy - Perechuda, Kazimierz (The knowledge diffusion to the local administration of a commune council, 2005)
In the paper are presented: local administration as the net organization, the asymmetry of the diffusion of the tacit knowledge in the local government, the geometry of the net of the territorial division.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 314-319